2018
DOI: 10.1259/dmfr.20170251
|View full text |Cite
|
Sign up to set email alerts
|

Lingual tonsillolith: prevalence and imaging characteristics evaluated on 2244 pairs of panoramic radiographs and CT images

Abstract: Lingual tonsilloliths commonly appear on CT. They also appear on panoramic radiography and may superimpose the surrounding soft tissue of the mandible. Although lingual tonsilloliths may resemble other pathological calcifications including submandibular sialoliths and lingual osseous cholistoma, they can be differentiated by carefully observing panoramic radiographs. When clinicians detect calcified bodies near the base of tongue, lingual tonsilloliths should be included in the differential diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
1
15
0
3
Order By: Relevance
“…[8][9][10][11][12][13] In addition, lingual tonsilloliths are commonly encountered with a prevalence of 4.8%. 14 Compared to those, NT and ET are much less prevalent and smaller among the same population. 11,13,14 This may be explained by the sizes of the nasopharyngeal and eustachian tube tonsils, which become smaller than the palatine tonsils following the preadolescence period, making it difficult for NT and ET to grow larger in size.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[8][9][10][11][12][13] In addition, lingual tonsilloliths are commonly encountered with a prevalence of 4.8%. 14 Compared to those, NT and ET are much less prevalent and smaller among the same population. 11,13,14 This may be explained by the sizes of the nasopharyngeal and eustachian tube tonsils, which become smaller than the palatine tonsils following the preadolescence period, making it difficult for NT and ET to grow larger in size.…”
Section: Discussionmentioning
confidence: 97%
“…14 Compared to those, NT and ET are much less prevalent and smaller among the same population. 11,13,14 This may be explained by the sizes of the nasopharyngeal and eustachian tube tonsils, which become smaller than the palatine tonsils following the preadolescence period, making it difficult for NT and ET to grow larger in size. Furthermore, in this study, we occasionally encountered a pocket-like depression or pouch on the mucosal surface of the nasopharynx (Figure 4), which may have been caused by the dislodgement of ET, eustachian tube tonsilloliths; NT, nasopharyngeal tonsilloliths.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tonsilloliths are oropharyngeal concretions that form within the palatine tonsillar crypt in reaction to a foreign nidus such as bacteria or organic debris. As it has been suggested that tonsilloliths are related clinically to halitosis and tonsillar abscess, these structures are of interest in the field of dentistry [1][2][3][4][5][6][7][8]. Tonsilloliths can be visualized on digital panoramic radiographs [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…They may be asymptomatic or cause dysphagia, globus sensation, halitosis, otalgia, peritonsil-lar abscess, swelling in the tonsillar fossa, glossopharyngeal neuralgia, orofacial pain, upper airway obstruction, and sleep breathing disorders. They may be incidentally found in three-and two-dimensional radiological examinations [1][2][3][4][5][6][7][8][9][10][11][12][13]. TLs appear as small opacities, overlapping the middle portion of mandible ramus, or as multiple poorly defined radio-opacities, which may be oval, round, or irregular in shape, superimposed on the soft tissues' shadows.…”
Section: Introductionmentioning
confidence: 99%